(untitled) (International Journal of Financial, Administrative and Economic Sciences, 2025)
The study mainly aimed to identify the nature of the relationship between the work environment axes and administrative creativity in the Commercial Farmers Bank. To achieve the study objectives, the descriptive analytical approach was followed for its suitability to the nature of the study. The researcher designed a questionnaire that included (450) items to collect primary information from the respondents. In light of this, the data were collected and analyzed and the study hypotheses were tested. The main hypothesis is that there is no statistically significant effect of the work environment factors (organizational structure, systems and instructions, training, participation in decision-making, incentives and rewards, and technology). The most important results reached by the study were that there is a statistically significant effect of the organizational structure on administrative creativity and there is no statistically significant effect of incentives and rewards on administrative creativity. The study concluded with a set of recommendations, the most important of which is to focus on accurately and clearly describing jobs and working to reformulate the system and standards of promotions for employees, setting systems and instructions that adapt to the work environment to avoid confusing and delaying work, and avoiding issuing conflicting instructions from more than one official.